Bilingual Children With Nonsyndromic Cleft Lip and/or Palate: Language and Memory Skills. - Young, Selena Ee-Li; Purcell, Alison Anne; Ballard, Kirrie Jane; Liow, Susan Jane Rickard; Ramos, Sara Da Silva; Heard, Robert; Oetting, Janna; Hustad, Katherine (Journal of Speech, Language & Hearing Research, 2012)
Purpose: Research shows that monolingual children with cleft lip and/or palate (CLP) have a higher incidence of cognitive-linguistic deficits, but it is not clear whether bilingual preschool children with CLP are especially vulnerable because they need to acquire 2 languages. We tested the hypothesis that bilingual children with CLP score lower than bilingual children with typical development (TD) on receptive vocabulary, verbal memory, and visuospatial memory. Method: Participants were 86 bilingual CLP children and 100 TD children 3-6 years of age, dominant in English or Mandarin. Each child completed assessments of English and Mandarin vocabulary, verbal and visuospatial short-term and working memory, hearing, and articulation. Results: With analysis of covariance controlling for age and dominant language, no group differences were found between the CLP and TD bilingual children, although a correlational analysis indicated discrepancies in the relationship between variables. Conclusions: The findings do not support the hypothesis that preschool children with CLP score lower than preschool children with TD on receptive vocabulary and memory measures. Longitudinal research examining literacy skill development is needed to establish whether the deficits reported for school-age monolingual children with CLP become more obvious in bilingual children in later years, especially when the medium of instruction is the child's nondominant language.